Andersoniodoxa, a replacement name for Andersoniella (Malpighiaceae) - Davis, Charles C.; Marinho, Lucas C.; Amorim, André M. (Phytotaxa, 2020)
Subsequent to our recent publication honoring William R. Anderson (Davis et al., 2020), we discovered the publication of an obscure monotypic genus of algae, Andersoniella F. Schmitz (1897: 520), that is nowadays recognized as a synonym of Leptocladia J.Agardh (1892: 95) (Schneider & Wynne, 2007). This immediately rendered our name a later homonym at the time of its publication (Turland et al., 2018). We are correcting this misstep here by recognizing the replacement name Andersoniodoxa, meaning “the glory of Anderson”. See our recent description of Andersoniella for further details on the character diagnosis of this genus, illustrations, key for identification, its phylogeny, and representative specimens (including types) (Davis et al., 2020).